கேரளத்தில் தமிழ்க்கல்வி / Tamil Education in Kerala - முனைவர் அ. ஹெப்சி ரோஸ் மேரி / Dr. A. Hepsy Rose Mary (International Journal of Tamil Language and Literary Studies, 2023)
Kerala was a part of the ancient Tamil Nadu. They were having close ties in culture and language. Sangam Literature lies as a testimony to the connection between Tamil Nadu and Kerala. There are 350 songs related to Chera Country in Sangam Literature. Now, Kerala is a place of multi-ethnic and multi-lingual people living together. Even though the language spoken in Kerala is Malayalam, it can be seen that there is an environment of learning and teaching other languages from school education onwards. In this way, people speaking many languages live together, there are many cultural changes occur among them. This article discusses the history of Kerala Tamizhians and the context of learning Tamil in Kerala from schooling to graduation; It also examines the reasons behind the majority of Tamizhians dropping out of Tamil education and this article also aims to highlight the methods to make them learn Tamil.